2012
DOI: 10.4143/crt.2012.44.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor: Is It a Feasible Target for the Treatment of Osteosarcoma?

Abstract: PurposeFeatures of epidermal growth factor receptor (EGFR) expression in osteosarcoma and in vitro efficacies of EGFR inhibitors against osteosarcoma cells were evaluated.Materials and MethodsThirty biopsy samples of osteosarcoma patients were retrospectively analyzed for EGFR protein expression by immunohistochemistry. Relationships between EGFR expression and clinicopathologic characteristics and treatment outcomes were evaluated. Four osteosarcoma cell lines were analyzed for EGFR and p-EGFR expression by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 21 publications
(29 reference statements)
3
36
0
Order By: Relevance
“…The histological feature is the formation of osteoid tissue. The disease metastasizes in early stage and minimal pulmonary metastasis occurs in 80% of patients (Lee et al, 2012). Microvessel consist of tiny vessels and capillaries, the distribution of microvessel of carcinoma is among oncocyte.…”
Section: Introductionmentioning
confidence: 99%
“…The histological feature is the formation of osteoid tissue. The disease metastasizes in early stage and minimal pulmonary metastasis occurs in 80% of patients (Lee et al, 2012). Microvessel consist of tiny vessels and capillaries, the distribution of microvessel of carcinoma is among oncocyte.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 90% of 27 OS biopsy samples showed moderate-to-high EGFR protein levels, as well as in four established OS cell lines HOS, KHOS/NP, MG-63, and U-2 OS . EGFR expression was not found to correlate to response to preoperative chemotherapy or survival [58]. Another group demonstrated that OS cell lines, MG-63 and Saos-2 proliferative abilities, were decreased by natural lavonoid Icariside II.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The expression of ErbB1 has been reported in 30-90% of tumor tissues (26)(27)(28); however, correlations between ErbB1 expression and clinical prognosis have been controversial. The study by Kersting et al (29) found that all patients with strong ErbB1 expression were alive for up to 12 years after diagnosis (overall survival), irrespective of the degree of neoadjuvant chemotherapy and induced tumor regression, which indicted that expression of ErbB1 in high-grade osteosarcoma showed a positive dose-response relation with favorable clinical outcome.…”
Section: Erbb1 In Osteosarcomamentioning
confidence: 99%
“…Wu et al (31) performed a clinical study and constructed a mediation model to explain and confirm the correlation pattern of ErbB1 and the AKT signal pathway for cancer cell proliferation in osteosarcoma patients. Lee et al (28) found that loss of PTEN in tumors with ErbB1 expression was associated with resistance to anti-ErbB1 tyrosine kinase inhibitors. However, Freeman et al (33) did not identify a correlation between ErbB1 expression, or PTEN, and clinical features.…”
Section: Erbb1 In Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation